Improving the Properties of Laccase Through Heterologous Expression and Protein Engineering - Guoqiang Guan; Beidian Li; Ling Xu; Jingya Qian; Bin Zou; Shuhao Huo; Zhongyang Ding; Kai Cui; Feng Wang (Microorganisms)
Laccase, a member of the blue multicopper oxidase family, is widely distributed across diverse taxonomic groups, including fungi, bacteria, plants, and insects. This enzyme drives biocatalytic processes through the oxidation of phenolic compounds, aromatic amines, and lignin derivatives, underpinning its significant potential in the food industry, cosmetics, and environmental remediation. However, wild-type laccases face critical limitations, such as low catalytic efficiency, insufficient expression yields, and poor stability. To address these bottlenecks, this review systematically examines optimization strategies for heterologous laccase expression by fungal and bacterial systems. Additionally, we discuss protein engineering for laccase modification, with a focus on the structural basis and active-site redesign. The comprehensive analysis presented herein provides strategic suggestions for advancing laccase engineering, ultimately establishing a theoretical framework for developing high-efficiency, low-cost engineered variants for large-scale biomanufacturing and green chemistry applications.